2020
DOI: 10.3390/ijerph17103482
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Musculoskeletal Diseases and Pain among Dental Professionals through Ergonomic Interventions: A Systematic Literature Review

Abstract: Musculoskeletal diseases and pain (MSDs) are prevalent among dental professionals. They cause a growing inability to work and premature leaving of the occupation. Thus, the objective of this review was to summarize the evidence of ergonomic interventions for the prevention of MSDs among dental professionals. This review was conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The literature search was carried out in May 2018, with an update in April 2019. Scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 32 publications
(101 reference statements)
0
33
0
7
Order By: Relevance
“…Compared to many other studies [ 4 , 8 , 11 13 , 18 , 19 ], the lifetime and the 12-month prevalence of hand MSDs in Ds and DAs in the current study is lower. Advanced investigations and possibly, the implementation of ergonomic conditions in dentistry in recent years, may contribute to these differences [ 44 ]. Besides, most of the studies, including the present study, have adopted the Nordic Questionnaire [ 4 , 11 13 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to many other studies [ 4 , 8 , 11 13 , 18 , 19 ], the lifetime and the 12-month prevalence of hand MSDs in Ds and DAs in the current study is lower. Advanced investigations and possibly, the implementation of ergonomic conditions in dentistry in recent years, may contribute to these differences [ 44 ]. Besides, most of the studies, including the present study, have adopted the Nordic Questionnaire [ 4 , 11 13 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to relational measures, several ergonomic studies at the dental workplace confirm that an improvement in ergonomics (e.g. with regard to instruments, the practitioner's as well as the patient's chair and the arrangement of the working environment) leads to a decrease in MSDs [37,[41][42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…The nature of dental work, which includes repetitive movement, long work sessions and awkward static postures, contributes to musculoskeletal problems amongst dentists [ 1 ]. The costs of these problems are substantial, both in terms of money and in terms of work time lost [ 4 ]; these musculoskeletal problems may result in lower work productivity, have an adverse effect on the quality of work and efficiency, lead to a shortened working lifespan, and contribute to occupational disability, which constitute a major health challenge for individual and healthcare system around the world [ 5 , 6 ]. A study conducted by Oberg [ 7 ] found that the loss of income due to musculoskeletal pain in the dentistry profession is greater than $40 million.…”
Section: Introductionmentioning
confidence: 99%
“…Trying to combat these affections, the science of ergonomics searched for multiple methods to improve. Among those methods, magnification systems proved to be an efficient tool to combat ill posture and subsequently MSDs 16 . Magnification loupes, shown to have positive impact on the prevention of MSDs, 16 could improve students' working habits because students who have begun their clinical years are more prone to work‐related musculoskeletal disorders compared to students in their preclinical years 17 …”
Section: Introductionmentioning
confidence: 99%